Testing Consistency: Analyzing the Reliability of Two Lower Limb Isometric Force Measurements in Strength-Trained Athletes - Francisco Giuliano; Marcos A. Soriano; Victor Pino-Mulero; Jaime González-García (Applied Sciences)
This study aimed to examine the intra- and inter-session reliability of kinetic variables in the isometric mid-thigh pull (IMTP) and isometric belt squat test (IBSqT) in strength-trained individuals. Fifteen men (26.9 ± 8.9 years; 1.78 ± 0.05 m; 86.9 ± 10.5 kg) and six women (23.8 ± 4.6 years; 1.66 ± 0.06 m; 65.8 ± 10.3 kg), experienced in strength training, completed a familiarization session followed by two experimental sessions. The peak force (PF) and relative peak force to body weight (RPF), were collected for both isometric tests. Additionally, force (F), impulse (I), and rate of force development (RFD) were analyzed across different time windows (50, 100, 150, 200, and 250 ms). The intraclass correlation coefficient (ICC), coefficient of variation (CV), standard error of measurement (SEM), smallest worthwhile change (SWC) and Bland-Altman plots were calculated and displayed. Intra-session reliability was excellent for PF and RPF (ICC ≥ 0.98, CV ≤ 10%) in both IMTP and IBSqT. However, RFD and IMP displayed higher variability (CV > 10%), with low to good reliability depending on time frames. Inter-session reliability was excellent for PF and RPF (ICC ≥ 0.96, CV ≤ 5.3%) in both tests. Force at various time points exhibited moderate to excellent reliability (ICC = 0.70–0.90). PF and RPF demonstrated the highest sensitivity to performance changes, with SWC0.2 values exceeding SEM. In contrast, RFD and impulse showed larger variabilities. These findings indicate that PF and RPF are the most reliable and sensitive metrics for monitoring performance. Coaches and practitioners can use IMTP and IBSqT to detect meaningful changes in maximal isometric force production.